Chronic upregulation of activated microglia immunoreactive for galectin-3/Mac-2 and nerve growth factor following diffuse axonal injury - Venkatesan, Charu; Chrzaszcz, MaryAnn; Choi, Nicole; Wainwright, Mark S (Journal of neuroinflammation, 2010)
Background Diffuse axonal injury in patients with traumatic brain injury (TBI) can be associated with morbidity ranging from cognitive difficulties to coma. Magnetic resonance imaging scans now allow early detection of axonal injury following TBI, and have linked cognitive disability in these patients to white matter signal changes. However, little is known about the pathophysiology of this white matter injury, and the role of microglial activation in this process. It is increasingly recognized that microglia constitute a heterogeneous population with diverse roles following injury. In the present studies, we tested the hypothesis that following diffuse axonal injury involving the corpus callosum, there is upregulation of a subpopulation of microglia that express the lectin galectin-3/Mac-2 and are involved in myelin phagocytosis. Methods Adult mice were subject to midline closed skull injury or sham operation and were sacrificed 1, 8, 14 or 28 days later. Immunohistochemistry and immunofluorescence techniques were used to analyze patterns of labelling within the corpus callosum qualitatively and quantitatively. Results Activated microglia immunoreactive for galectin-3/Mac-2 were most abundant 1 day following injury. Their levels were attenuated at later time points after TBI but still were significantly elevated compared to sham animals. Furthermore, the majority of galectin-3/Mac-2+ microglia were immunoreactive for nerve growth factor in both sham and injured animals. Conclusions Our results suggest that galectin-3/Mac-2+ microglia play an important role in the pathogenesis of diffuse axonal injury both acutely and chronically and that they mediate their effects, at least in part by releasing nerve growth factor.